PENERAPAN TEKNOLOGI PENGENDALIAN HAMA TERPADU (PHT) PADA PERKEBUNAN RAKYAT JAMBU METE (Studi Kasus Petani Jambu Mete di Propinsi Nusa Tenggara Barat) - ADE SUPRIATNA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
This study was conducted in 2003 and took place in Nusa Tenggara Barat (NTB).The objectives of study were: to evaluate the implementation of the integrated pestmanagement School on farmer field (IPM-FFS), farmers adoption of IPM technology,changes of farm productivity and income. The result showed, that majority of farmershave controlled the pest based on principles of IPM. Firstly, the farmer do preventivecontrol by adopting some practices to make crops grow healthy, apply biological andmechanical control, and also use organic pesticide. Finally, if the intensity of pest's attackwere still in the level of economic injury the farmer would use chemical pesticide. Agroecosystemobservation has been adopted by alumni farmer (100%) and non-alumni (34,5%), mechanical control have been adopted by (100%) and non-alumni (66, 6%), andorganic pesticide have been adopted by alumni (6, 7%) and non-alumni (13, 3%). Whilethe application of chemical pesticide not be found because the intensity of pest attack wasstill low and the costly pesticide price push reduction of chemical pesticide use. Thealumni productivity was 300kg and non-alumni were 270 kg/ha/year. If all expenses offarm were counted, farm benefit of alumni and non-alumni would be disadvantage,namely Rp.206 thousand and Rp.287 thousand/ha/year, respectively. If family labor costwere not counted, they would be advantage, namely Rp.858 thousand and Rp.735thousand/ha/year, respectively. Then if all expenditure coming from property of farmer(family labor and organic fertilizer) were not counted, they would be advantage, namelyRp.890 thousand and Rp.771 thousand/ha/year, respectively. Based on statistical test,productivity and farm benefit of alumni and non-alumni were not different. Introducingthe low cost technology (IPM-FFS) is very suited for cashew nut farmer because theircapital are still low such as using organic pesticides available in their field, biological andmechanical control, and organic manure. Considering its progress, IPM-FFS is suggestedto overspread to other location.